Integration of Islamic Values ​​in Science Education 'A Reconstruction Effort in Education': Integrasi Nilai-Nilai Islam Dalam Pendidikan Sains ‘Sebuah Upaya Rekonstruksi dalam dunia Pendidikan’ - Wahyuni, Akhtim (Halaqa: Islamic Education Journal, 2020)
Islam and science are an inseparable unity. Islam as a religion is a source of knowledge and knowledge is a means to apply everything contained in religious teachings. In the Qur'an, there are around 750 verses related to science. This shows that Islam places great emphasis on the development of science. But what happens, these two things are pushed aside from each other, resulting in a dichotomy of knowledge that enters all aspects of life. The awareness to restore the position of Islam and science began to be rolled back by Muslim thinkers by integrating the two. In educational institutions, the integration of Islamic and science values ​​is strengthened through an "integrated curriculum", which is "bringing together several scientific disciplines in a learning design to obtain better learning outcomes with the ability of students to connect one subject to another. Among the integration concepts offered are "shared, Webbed, and integrated." In addition to curriculum integration, components that need to be considered are improving the quality of human resources and educational infrastructure.